Destination Heartland : a guide to discovering the Midwest's remarkable past - Clampitt, Cynthia (3 Fields Books, an imprint of University of Illinois Press, 2022)
"The Midwest's place at the crossroads of the nation makes it a rich travel destination for anyone interested in the history and heritage of the United States. Cynthia Clampitt's guide to heartland historical sites invites readers to live the past, whether it's watching a battlefield reenactment or wandering the grounds of an ancient Native American city. From the National Underground Railroad Freedom Center to the Chinese American Museum, Clampitt uncovers the fascinating stories behind these quintessentially Midwestern places while offering valuable tips for getting the most out of your visit. She also ventures beyond the typical scope of guidebooks to include historic restaurants, small-town museums, and other overlooked gems perfect for turning that quick day trip into a leisurely itinerary. An informative handbook and love letter to the Midwest, Destination Heartland provides travelers with a knowledgeable companion on the highways and backroads of history. States covered in the book: Illinois, Indiana, Iowa, Kansas, Michigan, Minnesota, Missouri, Nebraska, North Dakota, Ohio, South Dakota, and Wisconsin"--